Characterization of yield stress surface and strain-rate potential for tubular materials using multiaxial tube expansion test method. (October 2020) - Nazari Tiji, Sobhan Alah; Park, Taejoon; Asgharzadeh, Amir; Kim, Hyunki; Athale, Madhura; Kim, Ji Hoon; Pourboghrat, Farhang
Abstract: A combined experimental and computational method was developed to characterize the yield stress surface and the conjugate plastic strain-rate potential of the AA7075-O extruded tube under biaxial tension and biaxial tension-compression stress states based on the plastic work equivalency assumption. In all the previous experimental investigations, the focus was on developing tube bulging experimental setup with PID capability to control pressure and axial feed to generate real-time proportional deformation in the stress space. In this paper, a more practical method is introduced in which the PID control is implemented into a finite element model with the von Mises yield function to generate the necessary pressure and axial feed that result in any desired proportional strain path in the mid-section of the tube in the tube bulging simulation. As expected, the application of FEM + PID generated boundary conditions in the tube bulging experiments resulted in slightly different deformation paths. However, the plastic work equivalency assumption was used to construct the yield stress surface and the plastic strain-rate potential for the tube at different plastic work levels. Finally, the parameters of the Yld2004–18p yield function were calibrated for AA7075-O aluminum tube with the measured principal stress and plastic strain rate ratios for three levels of accumulated plastic work, and it was shown that this tubular material displays nearly isotropic plasticity under tension-compression, and anisotropic plasticity under tension-tension stress states. Highlights: FEM+PID numerical model was developed for tube bulging experiments boundary conditions generation. Experimental setup was developed to characterize AA7075 extruded tube under biaxial tension and tension-compression. Yield surface and the conjugate plastic strain-rate potential of the AA7075 tube was characterized. Yld2004–18p yield function was calibrated based on the characterized yield surface and the conjugate strain-rate potential. The material showed nearly isotropic plasticity under tension-compression, and anisotropic plasticity under tension-tension.